Adsorption behavior of Cu(II) on microwave-activated lemongrass-derived carbon: isotherm and kinetic modeling - Lailan - Ni'mah; Mahfud - Mahfud; Sri Rachmania Juliastuti; Ramdiana - Muis (Konversi, 2026)
This study evaluates the adsorption performance, equilibrium behavior, and kinetic properties of Cu ions using microwave-activated carbon derived from lemongrass for acid mine drainage treatment. The precursor was carbonized at 300 °C for 2 h and subsequently activated under microwave irradiation to enhance its physicochemical properties. Batch experiments were conducted with adsorbent dosages of 2–7 g and a fixed contact time of 60 min, and the remaining Cu concentration was measured by atomic absorption spectrophotometry. An optimal dosage of 4 g achieved the highest removal efficiency of 54.18%. Equilibrium data were analyzed using the Langmuir and Freundlich isotherm models, with the Langmuir model providing a better fit, yielding a maximum adsorption capacity (qmax) of 3.60 mg/g, a Langmuir constant (KL) of 43,27 mol/L, and an R² of 0,9825, compared with KF 3,46 and an R² of 0,9677 for the Freundlich model. These findings indicate predominantly monolayer adsorption on homogeneous sites and kinetics consistent with a pseudo first order model.